"The Parable and Its Lesson" by S.Y. Agnon and the Thinking of Historical Alternativeness - Katsman, Roman (MiKAN, 2017)
The article observes the elements of alternative history in Agnon's Ir U'Mloa, focusing on the story "The Parable and Its Lesson" as a case study. Alternative history is considered here not in the narrow sense as a popular genre that is embedded, as most of the critics mistakenly suggest, in the postmodern situation, but rather as a method of thinking about history and its causality in terms of multiple possibilities, oscillation between them and choice. Agnon's writing applies this method on the levels of characters, plots, imagery and ideas. Its analysis, as demonstrated in the article, reveals the unfolding of the writer's possibilistic philosophy of history, and particularly of the history of the demolished Jewish community in Europe, as presented in his post-Holocaust stories of Ir u-mloa.